Depresiasi Rupiah, hutang luar negeri dan beban APBN - A D Uphadi (Economic Journal of Emerging Markets, 1997)
There is correlation between depreciation of rupiah-debt foreign and load debt foreign on APBN. They can be analyzed with monetary approach. Monetary management isbeing tested, how it can manage the declining of monetary condition. We hope that our economy mil be fine fyrmulated. In this context debt analysis can becontinued by combining many approaches.